Concentrating Immiscible Molecules at Solid@MOF Interfacial Nanocavities to Drive an Inert Gas–Liquid Reaction at Ambient Conditions. Issue 52 (27th November 2018) - Sim, Howard Yi Fan; Lee, Hiang Kwee; Han, Xuemei; Koh, Charlynn Sher Lin; Phan‐Quang, Gia Chuong; Lay, Chee Leng; Kao, Ya‐Chuan; Phang, In Yee; Yeow, Edwin K. L.; Ling, Xing Yi
Abstract: Gas–liquid reactions form the basis of our everyday lives, yet they still suffer poor reaction efficiency and are difficult to monitor in situ, especially at ambient conditions. Now, an inert gas–liquid reaction between aniline and CO2 is driven at 1 atm and 298 K by selectively concentrating these immiscible reactants at the interface between metal–organic framework and solid nanoparticles (solid@MOF). Real‐time reaction SERS monitoring and simulations affirm the formation of phenylcarbamic acid, which was previously undetectable because they are unstable for post‐reaction treatments. The solid@MOF ensemble gives rise to a more than 28‐fold improvement to reaction efficiency as compared to ZIF‐only and solid‐only platforms, emphasizing that the interfacial nanocavities in solid@MOF are the key to enhance the gas–liquid reaction. Our strategy can be integrated with other functional materials, thus opening up new opportunities for ambient‐operated gas–liquid applications. Abstract : Gas–liquid reactions form the basis of our lives, yet they suffer from poor reaction efficiency and are difficult to monitor in situ, especially at ambient conditions. An inert gas–liquid reaction between aniline and CO2 is driven at 1 atm and 298 K. Real‐time reaction monitoring was performed by selectively concentrating these immiscible reactants at the interface between metal–organic framework and solid nanoparticles.